A review of pretreatment of diasporic bauxite ores by flotation separation. (December 2017) - Gibson, B.; Wonyen, D.G.; Chehreh Chelgani, S.
Highlights: The Al/Si mass ratio of bauxite for feeding the Bayer process has to be more than 8. The Al/Si in diaspore is less than 6 and has to pretreat before feeding to the process. Flotation has been typically used to increase the mass ratio of Al/Si diaspore ores. This study reviewed how different flotation factors can effect on upgrading diaspore. Abstract: The Bayer process is a conventional method for refining bauxite in the production of alumina. The Al/Si ratio in bauxite before feeding to the process must be enriched to more than eight by reducing impurities (mainly aluminosilicates). Therefore, diasporic bauxite ores (Al/Si < 6) have to be upgraded by pretreatment methods to meet the required quality for the Bayer process. Flotation separation (direct or reverse) followed by flocculation as an efficient pretreatment method is the main beneficiation technique for upgrading diaspore. Diaspore pretreatment by flotation favors several conditions and possesses certain limitations. This study has systematically explored various effective flotation factors (particle size, surface electrical charge, collectors, depressants, dispersants, flocculation and aggregation) and limitations in the pretreatment of diaspore and has compiled optimum results for its beneficiation. The summary offers various approaches for the selective flotation of diasporic ores via different conditions and suggests perspectives for further investigation.